2021
DOI: 10.1109/access.2021.3108972
|View full text |Cite
|
Sign up to set email alerts
|

Rolling Element Fault Diagnosis Based on VMD and Sensitivity MCKD

Abstract: In order to improve the diagnosis accuracy and solve the weak fault signal of rolling element of rolling bearings due to long transmission path, a novel fault diagnosis method based on variational mode decomposition (VMD) and maximum correlation kurtosis deconvolution (MCKD), namely VMD-MCKD-FD is proposed for rolling elements of rolling bearings in this paper. In the proposed VMD-MCKD-FD, the vibration signal of rolling element of rolling bearings is decomposed into a series of Intrinsic Mode Functions (IMFs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(66 citation statements)
references
References 62 publications
0
54
0
Order By: Relevance
“…The simulation signal and actual vibration signal were selected to verify the effectiveness of the reported VMD-MCKD method. The experiment revealed that VMD-MCKD could effectively diagnose the rolling element faults with high accuracy [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The simulation signal and actual vibration signal were selected to verify the effectiveness of the reported VMD-MCKD method. The experiment revealed that VMD-MCKD could effectively diagnose the rolling element faults with high accuracy [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“… GI + CNN: The input is transformed to 2D greyscale pictures (GI), which are then fed into the MTL-CNN, which is based on the proposed CNN from [ 60 ]. VMD + MTL-CNN: To generate the multifusion input, each signal is decomposed into a sequence of intrinsic mode functions using variational mode decomposition and then channel wise joined [ 61 ]. Then, using the suggested MTL-CNN architecture, those series of intrinsic mode functions are fusioned channel wise for classification.…”
Section: Experimental Setup and Performance Analysismentioning
confidence: 99%
“…Therefore, the CACO algorithm takes on a global optimization ability. In addition, some new optimization algorithms have been proposed in recent years [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55].…”
Section: Chaotic Ant Colony Optimization Algorithmmentioning
confidence: 99%